TNF-α release capacity is suppressed immediately after hemorrhage and resuscitation - Arian Bahrami (Chinese Journal of Traumatology, 2017)
Purpose: It has been suggested that patients with traumatic insults are resuscitated into a state of an early systemic inflammatory response. We aimed to evaluate the influence of hemorrhagic shock and resuscitation (HSR) upon the inflammatory response capacity assessed by overall TNF-α secretion capacity of the host compared to its release from circulating leukocytes in peripheral circulation. Methods: Rats (8/group) subjected to HS (MAP of 30–35 mmHg for 90 min followed by resuscitation over 50 min) were challenged with Lipopolysaccharide (LPS), 1 μg/kg intravenously at the end of resuscitation (HSR-LPS group) or 24 h later (HSR-LPS24 group). Control animals were injected with LPS without bleeding (LPS group). Plasma TNF-α was measured at 90 min after the LPS challenge. In addition, whole blood (WB) was obtained either from healthy controls (CON) immediately after resuscitation (HSR), or at 24 h post-shock (HSR 24). WB was incubated with LPS (100 ng/mL) for 2 h at 37 °C. TNF-α concentration and LPS binding capacity (LBC) was determined. Results: Compared to LPS group, HSR followed by LPS challenge resulted in suppression of plasma TNF-α in HSR-LPS and HSR-LPS24 groups (1835 ± 478, 273 ± 77, 498 ± 200 pg/mL, respectively). Compared to CON the LPS-induced TNF-α release capacity of circulating leukocytes ex vivo was strongly declined both at the end of resuscitation (HSR) and 24 h later (HSR24) (1012 ± 259, 313 ± 154, 177 ± 63 ng TNF/mL, respectively). The LBC in WB was similar between CON and HSR and only moderately enhanced in HSR24 (57 ± 6, 56 ± 6, 71 ± 5 %, respectively). Conclusion: Our data suggest that the overall inflammatory response capacity is decreased immediately after HSR, persisting up to 24 h, and is independent of LBC.